(untitled) (Current Horticulture, 2024)
An experiment was conducted to assess the performance of leafy vegetable purpose fenugreek under different shade net under Saurashtra agro climatic zone of Gujarat during summer 2013-14 to 2015-16 at Agricultural Research Station (Fruit Crops), Junagadh Agricultural University, Mahuva. The experiment comprised five treatments consisting 50% green shade net, 75% green shade net, 50% white shade net, 75% white shade net and no shade net (open). The 75% white shade net produced highest plant height (14.13 cm) and green yield (1.13 kg/m2) of fenugreek. Thus, it is quite logical that higher yield of green fenugreek in summer season can be obtained by using 75% white shade net house under Saurashtra condition.